"REVOLUTIONIZING E-LEARNING IN INDUSTRIAL MANAGEMENT: A GROUNDBREAKING EXPLORATION OF IM126 APPS AND UNDERGRADUATE PERSPECTIVES ON THEIR EFFECTIVENESS" - Faizan Abd Jabar; Mohd Faizal Azrul Azwan Che Harun; Nur Fakhzan Marwan; Muhammad Zainuddin Mohamed Azudin; Mohd Azharul Azemi (Journal of Islamic, Social, Economics and Development, 2023)
Over the past decade, the internet has provided unprecedented access to education and new skill acquisition through online learning platforms. With the onset of the COVID-19 pandemic, remote working and learning have become the norm for many institutions, necessitating the adoption of online learning methods. Consequently, the IM126 app has been designed and developed by a team of dedicated educators for Industrial Management (MGT 126) students, with the aim of enhancing the e-learning experience through improved interaction and a centralized platform for subject information. This study attempts to evaluate the effectiveness of the IM126 app as a comprehensive resource for Industrial Management information and to explore students' perceptions of the app as a facilitator of e-learning. Employing descriptive analysis through the Statistical Package for Social Science (SPSS) version 25, the study reports several benefits accrued by students from the app, including increased efficiency in document management and a high degree of effectiveness during e-learning sessions. These findings underscore the IM126 app's potential as a model for other subjects and suggest that universities should encourage the development and deployment of similar learning apps to support students and lecturers in navigating the challenges associated with the present era of remote learning.